Intra-party Conflict and the Emergence of Islamic-Based Parties in the post-2019 Election in Indonesia - Ari Ganjar Herdiansah (Universitas Sultan Ageng Tirtayasa, 2021)
This article explains the emergence of new Islamic-based parties after the-2019 election in Indonesia. They are Ummah Party, Masyumi-Reborn Party, and Gelora Party. By using intra-party conflicts and path dependency theories, this study reveals that the emergence of those new Islamic parties is associated with frictions among party actors that troubled their prior parties, namely PAN, PBB, and PKS. The formation of the Ummah Party and Masyumi-Reborn Party was also situated by the 2014 and 2019 political contest, which represent the oppositional stance that could not be accommodated by the prior parties. Meanwhile, Gelora Party offered itself as a middle ground between the pro and contra camps of the government and provided a solution for the Islamic conservatism. This article argues that the emergence of new Islamic parties continues a pattern that has long plagued Indonesian Islamic-based parties, namely political fragmentation.